2010
DOI: 10.1007/s12132-010-9107-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Development Planning in South Africa: Lessons from the Dwars River Valley

Abstract: Post-apartheid South Africa has brought about internationally acclaimed legislation that promotes social equity and environmental sustainability. This paper presents findings of research conducted in the Municipality of Stellenbosch on the effectiveness of the participatory planning model, the Integrated Development Plan (IDP). While post-apartheid accomplishments are noteworthy, power dynamics and fiscal insecurity continue to shape outcomes. Innovative coalitions have emerged, instilling hope that true parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This is unacceptable in African countries that are in dire need of resources to turn around their low growth rates (Nicolson 2015). Perhaps this, in a number of African countries, such as South Africa, points to a possibility that poor implementation of government policy could be one of the hugest challenges besetting the expansion of road networks in the rural areas where the bulk of the people live (Cash and Swatuk 2011;Komma 2012).…”
Section: Poor State Of Road Networkmentioning
confidence: 99%
“…This is unacceptable in African countries that are in dire need of resources to turn around their low growth rates (Nicolson 2015). Perhaps this, in a number of African countries, such as South Africa, points to a possibility that poor implementation of government policy could be one of the hugest challenges besetting the expansion of road networks in the rural areas where the bulk of the people live (Cash and Swatuk 2011;Komma 2012).…”
Section: Poor State Of Road Networkmentioning
confidence: 99%
“…However, in practice, there are countries where public participation is mandatory and those where it is not mandatory. According to Mason (2010) and Poncelet (2012), in Europe, public participation is enforceable through the Aarhus Convention (Mason, 2010: 10); in India, it is enforceable through Executive Order 13715 (Whyte, 2011: 200) (Connelly, 2010;Todes, Karam, Klug & Malaza, 2010) and integrated development planning (Todes, 2004;Cash & Swatuk, 2011) appear to be characterised by procedural injustices. Moreover, the criteria of PJ require more than public participation (representation).…”
Section: Participation/ Proceduralmentioning
confidence: 99%
“…Moreover, it facilitates communication, alleviates poverty, facilitates budgeting, ensures local corporate governance and thereby helps to overcome the apartheid legacy in South Africa (Venter, 2007). However, the poor planning and implementation of development initiatives is the biggest challenge in South Africa (Cash & Swatuk, 2011;Komma, 2012). Davids et al (2009) also identified five pitfalls of IDP, as follows:…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been noted that many South African local authorities have been producing IDPs, in order to comply with the policy and legal requirements. However, the poor planning and implementation of development initiatives is the biggest challenge in South Africa (Cash & Swatuk, 2011;Komma, 2012).…”
Section: Introductionmentioning
confidence: 99%